Polymorphisms in the ASAP1 and SP110 Genes and Its Association with the Susceptibility to Pulmonary Tuberculosis in a Mongolian Population - Xiaogang Cui; Tianqi Yuan; Pengyuan Ning; Jie Han; Yue Liu; Jiao Feng; Fan Lian; Mingyuan Hao; Li Dong; Jinqi Hao; Li Xing; Changxin Wu (Journal of Immunology Research)
Tuberculosis (TB) remains one of the deadliest infectious diseases in the world. Previous genome-wide association studies suggested that single-nucleotide polymorphisms (SNPs) in some genes could indicate the susceptibility to TB in some populations. Herein, we studied the association of SNPs in the immunity-related genes, i.e., ASAP1 and SP110 genes with the susceptibility to TB in a Mongolian population in China. A case–control study was performed with 197 TB patients and 217 healthy controls. Six SNPs in ASAP1 and six SNPs in SP110 were selected for genotyping test by second-generation sequencing technique. A SNP in SP110 gene (rs722555) was identified to be associated with susceptibility to TB in the Mongolian population (p<0.05). The T allele of rs722555 in SP110 gene was associated with a 36% increase of risk at TB (OR 1.36, 95% CI 1.03–1.81), and the CT+TT genotype of rs722555 was associated with a 74% increase of risk at TB (OR 1.74, 95% CI 1.16–2.60) in the dominant genetic model. None of SNPs in ASAP1 gene tested in this study were significantly associated with TB susceptibility, while some individuals with SNPs (rs10956514, rs4733781, rs2033059, rs12680942, rs1017281, rs1469288, and rs17285138) in the ASAP1 gene tended to have a reduced risk at TB. In conclusion, this study suggested that the rs722555 SNP in SP110 gene might be a risk factor for TB in a Mongolian population.